DECOMPOSITION OF PHASE D IN THE LOWER MANTLE AND THE FATE OF DENSE HYDROUS SILICATES IN SUBDUCTING SLABS - Shieh S.R.; Mao H.K.; Hemley R.J.; Ming L.C. (My University, 1998)
High pressure, high temperature quench-type experiments were carried out on serpentine to pressures of 53 GPa and temperatures between 800-1800°C. X-ray analyses show that recovered phase assemblages varied considerably for the different high pressure and high temperature studies. The dense hydrous magnesium silicate phases decompose sequentially as the pressure increases and appear to serve as reservoirs for H2O in the mantle, eventually releasing it at the highest pressure. Superhydrous phase B is stable up to pressure equivalent to the boundary between the transition zone and lower mantle. Phase D decomposes at pressures of 44 GPa, equivalent to about 1250 km depth. This may define the lower depth limit for the presence of dense hydrous magnesium silicates. Beyond this pressure, only nominally anhydrous phases have been recovered in high-pressure experiments. This may indicate a lack of stoichiometric-hydrogen bearing silicate phases at higher pressure.
Keywords: X-RAY DIFFRACTION ANALYSIS; LOWER MANTLE; SERPENTINE; HIGH PRESSURE